2020
DOI: 10.1080/13416979.2020.1747150
|View full text |Cite
|
Sign up to set email alerts
|

Growth-inhibitory activity of components in Cryptomeria japonica leaves against Robinia pseudoacacia

Abstract: Extracts obtained from Cryptomeria japonica leaves were tested for growth inhibition activity against Robinia pseudoacacia seeds, which is known as a representative invasive plant in temperate forests. Inhibitory activities against radicle and hypocotyl growth were found in hexane and ethyl acetate extracts but showed no or weak activity on seed germination. The extracts also showed inhibitory activity against Trifolium repens as a representative weed. The active extracts were fractionated by silica gel column… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…More recently, some other C. japonica bioactivities have been described. For instance, Tanaka et al [64] reported that chemical components of C. japonica leaves suppress the growth of invasive plants (Robinia pseudoacacia) and weeds (Trifolium repens), which are the largest competitor of agricultural crops, with negative impact on productivity.…”
Section: Other Biocidal Activities Of C Japonica Eomentioning
confidence: 99%
“…More recently, some other C. japonica bioactivities have been described. For instance, Tanaka et al [64] reported that chemical components of C. japonica leaves suppress the growth of invasive plants (Robinia pseudoacacia) and weeds (Trifolium repens), which are the largest competitor of agricultural crops, with negative impact on productivity.…”
Section: Other Biocidal Activities Of C Japonica Eomentioning
confidence: 99%
“…Pinus thunbergii (Japanese black pine) is native to Japan and Korea and is currently widely distributed in China due to its evergreen attributes, fast growth, and salinity tolerance [1]. It plays essential roles in ecological restoration, such as sand fixation and afforestation [2][3][4]. Despite the ecological effects, P. thunbergii in China were infected by many pathogens, which caused the wilt and mortality of pine trees.…”
Section: Introductionmentioning
confidence: 99%
“…(Japanese black pine) is a widely distributed pine species in China due to its graceful leaf shape, fast growth, and salinity tolerance, which originated from Japan and North Korea [6]. It plays essential roles in ecological restoration such as sand fixation, and environment afforestation [7]. However, in June 2020, a large area of P. thunbergii were observed to show discolored and withered needles in forests from Bazhong City, Sichuan Province, China.…”
Section: Introductionmentioning
confidence: 99%